Royal Gift Exchange between Mycenae and Egypt: Olives as "Greeting Gifts" in the Late Bronze Age Eastern Mediterranean - Kelder, J (Archaeological Institute of America, 2013)
Contacts between Egypt and the Aegean during the Late Bronze Age, especially focusing on the relation between Minoan Crete and New Kingdom Egypt have been the subject of much study. The relation between the Greek (Mycenaean) mainland and Egypt generally is regarded as a more elusive topic, and most scholars seem to consider contact between the two a matter of irregular exchange, probably not even a direct exchange, but via middlemen (on Cyprus, in the Levant etc.). In this paper, data on the import of Mycenaean stirrup jars -generally regarded as containers for olive oil- in Egypt and the presence of the olive (oil) in Egypt are presented. Both archaeological and paleobotanical data are examined. The aim of the paper is to stimulate new thought on the possibility that contact, or rather, exchange, between Egypt and the Greek mainland was more than an irregular phenomenon and was instead highly organized, involving the active engagement of the ruling elite at Mycenae and the Pharaonic court. At the same time, it will be demonstrated that olives or olive oil were of importance in this Late Bronze Age interstate contact.